GAMBARAN HARD WORKING PADA OWNER TAZE FOOD AND DRINK DI KOTA PEKANBARU - Nora Afriza; Yanladila Yeltas Putra (Edu Sociata : Jurnal Pendidikan Sosiologi, 2023)
This study intend to describe the hard working of settled foreigner who is entrepreneur and builds a business from the beginning to be able to develop his business until now. This study uses a phenomenological qualitative approach with using milles and huberman’s data analysis techniques was chosen as the research method because it’s in accordance with the research purposes. Data collection uses in-depth interviews with an overseas entrepreneur who has been abroad for more ten years and have a business for two years selected based on the purposive sampling. In this study found 15 sub-themes related to hard working that is decision to leave, business decision, never give up, see opportunity. Hard work, believe in ability, willingness to learn, like challenges, flexible, take into account risk, commitment, parental role and employee loyalty